Double-Headed Cationic Lipopeptides: An Emerging Class of Antimicrobials - Izabela Małuch (International Journal of Molecular Sciences, 2020)
Antimicrobial peptides (AMPs) constitute a promising tool in the development of novel therapeutic agents useful in a wide range of bacterial and fungal infections. Among the modifications improving pharmacokinetic and pharmacodynamic characteristics of natural AMPs, an important role is played by lipidation. This study focuses on the newly designed and synthesized lipopeptides containing multiple Lys residues or their shorter homologues with palmitic acid (C16) attached to the side chain of a residue located in the center of the peptide sequence. The approach resulted in the development of lipopeptides representing a model of surfactants with two polar headgroups. The aim of this study is to explain how variations in the length of the peptide chain or the hydrocarbon side chain of an amino acid residue modified with C16, affect biological functions of lipopeptides, their self-assembling propensity, and their mode of action.